2017
DOI: 10.3892/ol.2017.6394
|View full text |Cite
|
Sign up to set email alerts
|

Protoporphyrin IX-mediated sonodynamic therapy promotes autophagy in vascular smooth muscle cells

Abstract: Sonodynamic therapy (SDT) is effective in treating intimal hyperplasia and promoting plaque stability in animal models. The present study aimed to evaluate the effects of SDT with the sonosensitizer protoporphyrin IX (PpIX) on vascular smooth muscle cell (VSMC) viability and autophagy. Cultured VSMCs cells were divided into the following groups: i) Control, ii) ultrasound, iii) PpIX and iv) SDT. Flow cytometry and laser confocal detection were used to measure Annexin V stained VSMCs following different treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have reported that different ultrasonic intensities combined with diverse sound-sensitive agents produce distinct biological effects on specialized cells and tissues [26][27][28]. In this study, we demonstrated that when DVDMS was used in conjunction with ultrasound (diameter: 3.5 cm; resonance frequency: 0.5 MHz; duty factor: 10%; repetition frequency: 100 Hz) on the SCLC H446 cell line, apoptosis was observed.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have reported that different ultrasonic intensities combined with diverse sound-sensitive agents produce distinct biological effects on specialized cells and tissues [26][27][28]. In this study, we demonstrated that when DVDMS was used in conjunction with ultrasound (diameter: 3.5 cm; resonance frequency: 0.5 MHz; duty factor: 10%; repetition frequency: 100 Hz) on the SCLC H446 cell line, apoptosis was observed.…”
Section: Discussionmentioning
confidence: 57%
“…However, the effect was suppressed when the cell uptake of the particles was blocked by co-incubation with excess free folate (Brazzale et al, 2016). It is also reported that ROS generated by SDT is related to autophagy (Li et al, 2017; Kou et al, 2017). These findings indicates the possibility of a late-phase effect of ROS after TP-HIFU irradiation, warranting further experiments.…”
Section: Discussionmentioning
confidence: 97%
“…This nanocomplex has the capability to release CO 2 bubbles and trigger ultrasound-triggered inertial cavitation (UIC), which directly endorses ROS after the introduction of single injection stimulated by US. After experimentation, in vitro and in vivo results displayed the huge production of ROS, which increased tumor immunogenicity by promoting DC maturation that in return activated CD8 + T cells and inhibited tumors. , …”
Section: Enhancing Cancer Immunotherapy Through Ultrasoundmentioning
confidence: 99%
“…After experimentation, in vitro and in vivo results displayed the huge production of ROS, which increased tumor immunoge-nicity by promoting DC maturation that in return activated CD8 + T cells and inhibited tumors. 238,239 3.5.1. Mechanisms of Immune Activation through ROS.…”
Section: Enhancing Cancer Immunotherapymentioning
confidence: 99%